Magnetic resonance fetal right lung volumetry and its efficacy in predicting postnatal short‐term outcomes of congenital left‐sided diaphragmatic hernia. Issue 2 (22nd October 2013) - Hidaka, Nobuhiro; Ishii, Keisuke; Furutake, Yoko; Yamamoto, Ryo; Sasahara, Jun; Mitsuda, Nobuaki
Abstract Aim We aimed to investigate whether the ratio of magnetic resonance imaging (MRI)‐measured right lung volume (RLV) to ultrasonography‐estimated bodyweight (RLV/BW) and observed‐to‐expected (o/e) RLV are of diagnostic value in predicting postnatal outcomes of left congenital diaphragmatic hernia (CDH). Material and Methods We included 32 CDH patients and 34 control subjects. Manually outlined fetal right lung areas on MRI were multiplied by the slice thickness and added to determine the entire volume. The association between RLV and RLV/BW with gestational age in the controls was examined using regression analysis. RLV/BW and o/e RLV were compared between surviving and non‐surviving neonates with CDH. Results The expected fetal RLV was derived using the formula RLV (mm3) = 1.717 × (gestational weeks)2.82. In the controls, RLV/BW was nearly constant during the third trimester. The 27 survivors with CDH had a median RLV/BW of 10.7 and a median o/e RLV of 60.0, whereas the five non‐surviving neonates had a median RLV/BW of 4.3 and a median o/e RLV of 22.6; the differences were statistically significant. Conclusion Assessment of fetal lungs by MRI volumetry is reliable for clinical use. RLV/BW and o/e RLV are potential predictors of postnatal outcomes of left CDH.